Shifting paradigms: community engagement and utilization of recreational areas during and after COVID-19 - Maryanti Mohd Raid,; Nur Khairiyah Mohammad,; Norshafadila Ngadiman,; Zafirah Ab Muin,; Aminah Mohsin,; Amirul Haffiz Ariff, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The COVID-19 pandemic has shifted societal recreational practices due to the enforcing new norms, including movement controls, social distancing, and mask-wearing. This study aimed to examine how these new norms affected community recreational activities, both indoors and outdoors, in the endemic era. Therefore, the objectives of this study were twofold; i) to investigate the recreational activities conducted by the community during the pandemic; and ii) to evaluate the trends and community tendencies utilization of recreational spaces both indoors and outdoors during the endemic era. Employing a quantitative research design, a survey was randomly distributed to a sample of 200 respondents consisting of students and staff from Universiti Teknologi Malaysia (UTM). The collected data were analyzed using statistical methods and cross-tabulations through the Statistical Package for the Social Sciences (SPSS) to understand the recreational activities during the pandemic and the community preferences for using recreational areas indoors and outdoors. The findings provide insights into how societal recreational patterns have changed due to nearly two years of implementing new norms. Additionally, the study underscores the importance of recreational areas as a part of open spaces, particularly during the endemic era since they compete with indoor recreational facilities for community engagement.